ANALISIS BUTIR SOAL MATA KULIAH ALGORITMA PEMROGRAMAN - Yasinta Lisa (STKIP Persada Khatulistiwa Sintang, 2021)
ABSTRACTThis study aims to describe item analysis based on Bloom's taxonomy on the mid-semester test instrument for Programming Algorithms and Data Structures and its relation to student perceptions. The sample of the trial target is the Mid-Semester Test Question for the 2020/2021 Academic Year of the STKIP Persada Khatulistiwa Sintang Computer Education Study Program. The research method uses descriptive quantitative research. The results of the data analysis showed that, the results of the validity test stated that of the 30 questions (90%) there were 27 questions which were declared valid and 3 (10) questions invalid. Test the reliability of the test items obtained in the high category. The difficulty level of the questions ranges from 83.3% (Easy Questions), 10% (Medium Questions), and 6.7% (Difficult Questions). The Distinguishing Power of Questions in the moderate category and the Detractor Index have mostly functioned well. The distribution of cognitive levels is mostly at C1 (50%), C2 (23.3%), C3 (6.7%), C4 (10%), C5 (6.7%), and C6 (3.35) . This result is not proportional for the higher education level.Keywords: validity; reliability; level of difficulty; discriminatory power; cognitive level; item analysis.ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan analisis butir soal berdasarkan taksonomi bloom pada instrumen tes tengah semester mata kuliah Algoritma Pemrograman dan Struktur Data dan kaitannya dengan persepsi mahasiswa. Sampel sasaran uji coba yaitu Soal Tes Tengah Semester Tahun Akademik 2020/2021 Prodi Pendidikan komputer STKIP Persada khatulistiwa sintang. Metode penelitian menggunakan penelitian deskriptif kuantitatif. Hasil analisis data menunjukkan bahwa, hasil uji coba validitas menyatakan bahwa dari 30 soal (90%) terdapat 27 soal yang dinyatakan valid dan 3 (10) soal tidak valid. Uji Reliabilitas soal tes diperoleh pada kategori tinggi. Tingkat Kesukaran Soal berkisar 83,3% (Soal Mudah), 10% (Soal Sedang), dan 6,7% (Soal Sukar). Daya Pembeda Soal pada kategori cukup dan Indeks Pengecoh sebagian besar telah berfungsi dengan baik. Sebaran tingkatan kognitif sebagian besar berada pada C1 (50%), C2 (23,3%), C3 (6,7%), C4 (10%), C5 (6,7%), dan C6 (3,35). Hasil ini belum proporsional untuk tingkatan Perguruan Tinggi. Kata Kunci: validitas; reliabilitas; tingkat kesukaran; daya pembeda; tingkatan kognitif; analisis butir soal.